2017
DOI: 10.1002/ijc.31095
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of isoflavones and coumestrol and the risk of prostate cancer in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial

Abstract: Experimental studies have revealed that phytoestrogens may modulate the risk of certain sites of cancer due to their structural similarity to 17β-estradiol. The present study investigates whether intake of these compounds may influence prostate cancer risk in human populations. During a median follow up of 11.5 years, 2,598 cases of prostate cancer (including 287 advanced cases) have been identified among 27,004 men in the intervention arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Isoflavone and phytoestrogen intakes. In a PCS from the PLCO cohort [45], no statistically significant association was observed between intake of total isoflavones and risk of total or nonadvanced PCa. On the contrary, dietary intake of total isoflavones was associated with an increased risk of advanced PCa (HR [95% CI] 1.91 [1.25-2.92]; p trend 0.007).…”
Section: Dietary Factors and Pcamentioning
confidence: 83%
“…Isoflavone and phytoestrogen intakes. In a PCS from the PLCO cohort [45], no statistically significant association was observed between intake of total isoflavones and risk of total or nonadvanced PCa. On the contrary, dietary intake of total isoflavones was associated with an increased risk of advanced PCa (HR [95% CI] 1.91 [1.25-2.92]; p trend 0.007).…”
Section: Dietary Factors and Pcamentioning
confidence: 83%
“…Studies on the relationship between soy consumption and breast cancer risk are discordant, because foods rich in phytoestrogens, such as genistein, may have complex actions exerting both promotional and preventive effects (Table 1) [28]. As mentioned above, it should be noted that high consumption of genistein is associated with decreased risk of breast, lung, colorectal, ovarian, and endometrial cancers [126]. The use of natural compounds to alter molecular pathways in a clinical setting is currently being explored and provides hope for more control over treatment regimens in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses showed a protective effect of phytoestrogen and soy consumption against PCa [81,82]. However, the PLCO trial reported an increased risk of advanced PCa with isoflavone consumption [83].…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%